High-precision robotic assembly system using three-dimensional vision. (26th June 2021) - Yan, Shaohua; Tao, Xian; Xu, De
The design of a high-precision robot assembly system is a great challenge. In this article, a robotic assembly system is developed to assemble two components with six degree-of-freedoms in three-dimensional space. It consists of two manipulators, a structured light camera which is mounted on the end-effector aside component A to measure the pose of component B. Firstly, the features of irregular components are extracted based on U-NET network training with few labeled images. Secondly, an algorithm is proposed to calculate the pose of component B based on the image features and the corresponding three-dimensional coordinates on its ellipse surface. Thirdly, the six errors including two position errors and one orientation error in image space, and one position error and two orientation errors in Cartesian space are computed to control the motions of component A to align with component B. The hybrid visual servoing method is used in the control system. The experimental results verify the effectiveness of the designed system.